Analysis of the Low Level of Discipline of Class V Students SD Negeri 064961 Medan Maimun District - Billah Wulandari; Umar Darwis (International Journal of Educational Research Excellence (IJERE), 2023)
This Research Aims to Analyze the Low Level of Discipline of Class V Students of SD Negeri 064961 Medan Maimun District The research method used in this study is a descriptive method, namely a research method used to discuss a problem by researching, processing data, analyzing, and describing with detailed discussion. regularly and systematically with a qualitative approach. The approach in this study researchers used a qualitative approach. This research will examine the low level of discipline in fifth grade students at SD Negeri 064961 Kecanatan Medan Maimun. This research was conducted at SD Negeri 064961 Jl. Ps. Senen No. 40, Kp. Baru, Medan Maimun District, Medan City, North Sumatra. To obtain the desired data according to the problems in this thesis, the researchers used Observation techniques, Interviews, Questionnaires/Questionnaires, Documentation. First, authoritarian discipline, permissive discipline, and democratic discipline. These three ways have their respective goals in providing learning and student discipline education. This authoritarian discipline by giving reasonable to rigid behavior. Permissive discipline, namely giving freedom to overcome the problems at hand. Meanwhile, democratic discipline places more emphasis on rewards. These three methods are ways for educators to be applied in the teaching and learning process inside and outside the classroom while in the school environment.